To Lead or to Follow: Contribution of the Plant Vacuole to Cell Growth - Kaiser, Sabrina; Scheuring, David (Frontiers in Plant Science, 2020)
In contrast to animal cells, plant cells are surrounded by walls and thus, they cannot migrate. Therefore, cell elongation is a fundamental process for plant growth. To facilitate this process, a loosening of the rigid cell wall is required. On the other hand, vacuole size has been shown to correlate with cell size and inhibition of vacuolar expansion limits cell growth. However, the specific role of the vacuole during cell elongation is still not fully resolved. Especially the question whether the vacuole is the leading unit during cellular growth or just passively expands upon water uptake remains to be answered. Here, we review recent findings about the contribution of the vacuole to cell elongation. In addition, we also discuss the connection between cell wall status and vacuolar morphology. In particular, we focus on the question whether vacuolar size is dictated by cell size or vice versa and share our personnel view about the sequential steps during cell elongation.